Analisis dan Faktor Interaksi Obat Pada Pasien Hipertensi di Daerah Pesisir Surabaya - Faizah, Ana Khusnul; Nurrahman, Nani Wijayanti Dyah; Damayanti , Amitasari (Journal of Pharmaceutical and Sciences, 2025)
Hypertension is a severe health problem that generally requires combination therapy. Using a combination of antihypertensive therapy and long-term therapy requires monitoring the effects of potential drug-drug interactions (PDDIs) experienced by patients. This study aims to determine the drug interaction profile related to severity and mechanism. The method was descriptive and observational by recapitulating the prescription in several pharmacies in the coastal area of Surabaya. The samples are prescriptions consist of antihypertensives with other drugs. This research was conducted for three months. This study showed that 43% potential drug-drug interactions. The pharmacodynamic interactions are slightly more dominant (49%) than pharmacokinetics (45%). Meanwhile, the highest severity of drug interactions, namely minor (49%), followed by moderate (39%) and severe (12%), was in the last position. The modest drug interaction at a moderate level is amlodipine, which can decrease the pharmacological effect of metformin. Therefore, pharmacists need to monitor blood sugar levels regularly. Serious interactions are indeed the lowest incidence; otherwise, the effects can be dangerous, so pharmacists need to monitor patients who receive drugs with severe drug interactions. One of them is amlodipine and simvastatin, which can increase the risk of rhabdomyolysis from statins. Pharmacists have an important role in monitoring the effects of drug interactions in hypertensive patients. Patients get the maximum therapeutic effect with minimal drug interactions or prevent drug interactions.